Predicting Children’s Behavioral Problems Based on Marital Satisfaction, Phubbing, and Differentiation of Self with the Mediating Role of Mothers’ Resilience - Elyasi, Fahimeh (Mental Health and Lifestyle Journal, 2026)
The purpose of the present study was to predict children’s behavioral problems based on marital satisfaction, phubbing, and differentiation of self, with the mediating role of mothers’ resilience. The research method was descriptive-correlational. The statistical population included 4- to 6-year-old children and their mothers residing in districts 8, 9, and 10 of Tehran in 2025-2026. To select the research sample, 250 participants (mothers and children) were selected using a multi-stage cluster sampling method. Data were collected using the ENRICH Marital Satisfaction (EMS) scale, the Generic Scale of Phubbing (GSP), the Differentiation of Self Inventory-Revised (DSI-R), the Connor-Davidson Resilience Scale (CD-RISC), and the parent form of the Child Behavior Checklist (CBCL). Data analysis was performed using structural equation modeling. The results showed that there is a significant negative relationship between mothers’ marital satisfaction, differentiation of self, and resilience with children’s behavioral problems, and a significant positive relationship between mothers’ phubbing and children’s behavioral problems ( ). Furthermore, the results indicated that marital satisfaction, phubbing, and differentiation of self can indirectly predict children’s behavioral problems through the mediating role of mothers’ resilience.